EMOTIONAL WOUNDS THAT LEAVE SCARS: CASE STUDY OF THE EMOTIONAL DEVELOPMENT OF ADOLESCENTS WHO EXPERIENCE BULLYING - Syifa Awaliyah Nurrohmah; Ipah Saripah; Nadia Aulia Nadhirah (Universitas Pendidikan Indonesia, 2024)
The emotional wounds of teenagers who experience bullying are a concern. In the midst of this period of change, bullying can appear as a haunting shadow and leave deep emotional scars for the victims. The impact of bullying is not only physical wounds but also leaves deep emotional scars for the victims. This research aims to explore the impact of the emotional wounds experienced by teenagers due to the bullying they experience. Data obtained from a review of literature related to this topic. The results of the analysis show that the emotional wounds experienced by teenagers include low self-esteem, anxiety, loneliness, suicidal thoughts, self-isolation and depression. These findings illustrate how bullying affects the emotional aspects of teenagers in their daily lives, especially in their social relationships and learning.